Concurrent Validity of The U21 Men's Soccer Physical Test Battery - Tri Setyo Guntoro; Dewi Nurhidayah (Lambung Mangkurat University, 2024)
This study aims to test the validity of the U-21 men’s soccer physical test battery. The method used in this research is an evaluation approach. Data collection techniques in this research used tests and measurements. The subjects involved in this research were U-21 male soccer athletes in Papua. The total number of subjects participating in concurrent validity testing was 31 athletes. The instruments used in this research are body mass index (BMI) to measure body composition, sit and reach to measure flexibility, 30-meter sprint to measure speed, shuttle run to measure agility, leg and back dynamometer to measure muscle strength, and standing board. jump to measure explosive power, and the Multistage Fitness Test (MFT) to measure cardiovascular endurance. Validity testing uses a concurrent validity approach. The data analysis technique used in concurrent validity testing is using correlation product moment. This test is carried out by looking at the relationship between the tests on the first day and the second day. The results showed that each test item on the U-21 men’s soccer physical test battery had a calculated r value greater than the r table. Thus, it can be concluded that the U-21 Putra football physical test battery has a high validity value. Further research needs to test the reliability of the instrument to get a physical test instrument that meets the standards.